Study on the effects of Al–Ce composite deoxidations on the modification behaviors of TiN inclusions in 20CrMnTi steel - Shuang Liu; Fan Yang; Lixia Liu; Jian Wang; Jun Peng; Fang Zhang; Shengli An (Journal of Materials Research and Technology, 2024)
20CrMnTi gear steel has high low-temperature impact toughness and is widely used in the manufacturing of engineering machinery such as automotive transmission gears. The sizes and distributions of TiN inclusions have a significant impact on the service performances of 20CrMnTi gear steel. Controlling the growth behaviors and size distributions of TiN inclusions are the foundation for stable, high-quality, and efficient production of 20CrMnTi gear steel. This paper uses experimental and computational methods to study the effects of different ratios of Al–Ce composite deoxidizers on the modification behaviors of TiN inclusions in 20CrMnTi steel. The results show that the TiN inclusions in 20CrMnTi steel without Al–Ce composite deoxidizer are square in shape, with a size of approximately 4 μm. After Al–Ce composite deoxidation, a composite phase inclusion is formed in the steel, which has contracted edges and corners. The center is the nucleation core composed of elements such as Ce, Al, O, etc. The elements of Ti and N are wrapped around the periphery of the composite inclusion, reducing its size to 2 μm. When the ratio of Al and Ce in the Al–Ce composite deoxidizer is 7:3, the number of TiN inclusions in steel is the highest, accounting for 51.7% of the total amount of titanium inclusions. The average diameter of inclusions in the modified steel decreases to 2.4 μm. When the ratio of Al and Ce elements is 8:2 and 7:3, the final deoxygenation product is CeAlO3, which is more conducive to the modification of TiN inclusions in 20CrMnTi steel.